In Vitro Activity of Novel Antifungal Olorofim against Filamentous Fungi and Comparison to Eight Other Antifungal Agents - Georgacopoulos, Ourania (J Fungi (Basel), 2021)
Olorofim is a novel antifungal drug that belongs to the orotomide drug class which inhibits fungal dihydroorotate dehydrogenase (DHODH), thus halting pyrimidine biosynthesis and ultimately DNA synthesis, cell growth and division. It is being developed at a time when many invasive fungal infections exhibit antifungal resistance or have limited treatment options. The goal of this study was to evaluate the in vitro effectiveness of olorofim against a large collection of recently isolated, clinically relevant American mold isolates. In vitro antifungal activity was determined for 246 azole-susceptible Aspergillus fumigatus isolates, five A. fumigatus with TR(34)/L98H-mediated resistance, 19 Rhizopus species isolates, 21 Fusarium species isolates, and one isolate each of six other species of molds. Olorofim minimum inhibitory concentrations (MICs) were compared to antifungal susceptibility testing profiles for amphotericin B, anidulafungin, caspofungin, isavuconazole, itraconazole, micafungin, posaconazole, and voriconazole. Olorofim MICs were significantly lower than those of the echinocandin and azole drug classes and amphotericin B. A. fumigatus wild type and resistant isolates shared the same MIC50 = 0.008 μg/mL. In non-Aspergillus susceptible isolates (MIC ≤ 2 μg/mL), the geometric mean (GM) MIC to olorofim was 0.54 μg/mL with a range of 0.015–2 μg/mL. Olorofim had no antifungal activity (MIC ≥ 2 μg/mL) against 10% of the collection (31 in 297), including some isolates from Rhizopus spp. and Fusarium spp. Olorofim showed promising activity against A. fumigatus and other molds regardless of acquired azole resistance.